2016
DOI: 10.1089/jwh.2015.5681
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Headaches, and Sleep Health in High School Students

Abstract: These results are consistent with other studies of gender-based differences in sleep health and emphasize the importance of recognizing the risk of headache in female adolescents and treating that condition to prevent additional sleep health issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
(54 reference statements)
1
5
0
Order By: Relevance
“…Although they have a similar bedtime during the school week to their male counterparts, females wake up earlier on school mornings, obtaining less school night sleep and compensating by going to bed earlier on the weekend and obtaining more weekend night sleep. Previous research supports our findings of shorter TST School for female vs. male adolescents (Jiang et al, 2015; Ming et al, 2016; Ojio et al, 2016) but more research is needed on the between-sex differences in adolescent TST Weekend. The 5.4-min shorter TST School in females compared with males may seem like a modest difference but translates to a 27-min reduction in sleep duration across one week.…”
Section: Discussionsupporting
confidence: 88%
“…Although they have a similar bedtime during the school week to their male counterparts, females wake up earlier on school mornings, obtaining less school night sleep and compensating by going to bed earlier on the weekend and obtaining more weekend night sleep. Previous research supports our findings of shorter TST School for female vs. male adolescents (Jiang et al, 2015; Ming et al, 2016; Ojio et al, 2016) but more research is needed on the between-sex differences in adolescent TST Weekend. The 5.4-min shorter TST School in females compared with males may seem like a modest difference but translates to a 27-min reduction in sleep duration across one week.…”
Section: Discussionsupporting
confidence: 88%
“…The natural changes to the body’s sleep processes transform during adolescence; these changes also vary by gender, but research results are contradictory. Studies have found that adolescent females have poorer sleep quality, more difficulty falling asleep, and shorter sleep duration than their male counterparts (Galland et al., 2017; Marczyk Organek et al., 2015; Maslowsky & Ozer, 2014; Ming et al., 2016; Ohida et al., 2004; Wang et al., 2016). Other research has revealed that older adolescent males, but not their female counterparts, experience more disrupted sleep and more wakefulness after initially falling asleep than younger males (Baker et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that most of the studies included in this synthesis took place in North America, more precisely in the United States (Gilman et al, 2007;Heyer et al, 2014;;Pecor et al, 2015;Kemper et al, 2016;Ming et al, 2016;Lateef et al, 2019). None of the studies were conducted in Brazil.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that 80% of the studies have a cross-sectional design (Gilman et al, 2007;Grupta et al, 2008;Pecor et al, 2015;Kemper et al, 2016;Ming et al, 2016;Ming et al, 2016;Torres-Ferrus et al, 2018), thus, only demonstrating the association between the Research, Society and Development, v. 9, n. 10, e1019108247, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i10.8247 variables and preventing the cause and effect verification, only allowing to raise certain hypotheses. Therefore, the conclusions drawn from these studies should be cautiously considered.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation